2021
DOI: 10.4039/tce.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering survival of Drosophila suzukii (Diptera: Drosophilidae) in temperature regimes emulating partly protected winter conditions in a cold–temperate climate of Québec, Canada

Abstract: Field-acclimated Drosophila suzukii (Diptera: Drosophilidae) from the Saguenay–Lac-Saint-Jean region, Québec, Canada, were examined over two years for winter survival, under the hypothesis that flies select protected overwintering microhabitats. In 2016–2017, flies trapped alive in the field or emerged from infested fruits were submitted to four winter regimes of either constant or daily fluctuating temperatures of 5 °C (2–8 °C) or 10 °C (7–13 °C). In 2017–2018, two fluctuating regimes averaging either 1 °C (–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(77 reference statements)
2
7
1
Order By: Relevance
“…Despite substantial mortality after 180 days of cold stress, numerous D. suzukii flies of both sexes survived. When transferred to springtime rising temperatures and increased daylength based on regional norms, life expectancy distributions indicated that winter survivors (10-30% of flies tested) would still be alive in June and up to July of next year (Cloutier et al 2021). The flies were from lateseason, high-density populations (Champagne-Cauchon et al 2020), as previously reported (e.g., Thistlewood et al 2018).…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Despite substantial mortality after 180 days of cold stress, numerous D. suzukii flies of both sexes survived. When transferred to springtime rising temperatures and increased daylength based on regional norms, life expectancy distributions indicated that winter survivors (10-30% of flies tested) would still be alive in June and up to July of next year (Cloutier et al 2021). The flies were from lateseason, high-density populations (Champagne-Cauchon et al 2020), as previously reported (e.g., Thistlewood et al 2018).…”
Section: Introductionsupporting
confidence: 67%
“…Finding mates in spring would be the most critical factor at the low fly densities that are typical in spring, due to the Allee principle (Jacobs 2009), with decreasing available time and energy (Kramer et al 2009;Yamanaka and Liebhold 2009;Xu and Ma 2020). This would apply mostly to male D. suzukii, for which the odds of winter mortality are nearly twice those of females (Cloutier et al 2021), and as indicated by the results of our 2017 experiment (Supplementary material 1).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations